Recombinant Interleukin-1 receptor antagonist for the treatment of ST-segment elevation acute myocardial infarction prevents future heart failure events: a pooled analysis of the VCUART program. (25th November 2020) - Van Tassell, B; Wohlford, G.F; Ho, A.C; Vecchie, A; Garmendia, C; Trankle, C.R; Buckley, L.F; Kadariya, D; Canada, J.M; Carbone, S; Markley, R; Turlington, J.S; et al.
Abstract: Background: ST segment elevation myocardial infarction (STEMI) is associated with an intense acute inflammatory response and an increased risk of death and heart failure (HF). We analyzed the effect of recombinant interleukin-1 receptor antagonist (anakinra) 100 mg subcutaneous injection given once or twice daily for 14 days on the occurrence of HF in a pooled analysis of 3 clinical trials. Methods: Enrollment criteria and study procedures were the same across the three studies. High-sensitivity C-reactive protein (CRP) was measured at baseline, 72 hours, and 14 days to construct an area under the curve (AUC0–14). Clinical events up to 1 year were adjudicated by an independent committee blinded to treatment allocation. Data for anakinra once daily and anakinra twice daily were pooled into a single anakinra group. CRP data are presented as median and interquartile range to allow for deviation from Gaussian distribution and non-parametric tests were used to evaluate differences between groups. Kaplan-Meier survival analyses were conducted and the intervention groups were compared using a log-rank test. Results: Between 2008 and 2017, 139 patients with STEMI were enrolled. 84 patients were randomized to anakinra and 55 patients were randomized to placebo. Anakinra significantly reduced the CRP AUC0–14 (76 [42–147] vs 222 [117–339] mg*day/L; P<0.001), the composite of death or HF hospitalization (Chi2=7.167; P=0.007), and the composite of death or new onset HF (Chi2=9.43; P=0.002) compared with placebo. Treatment with anakinra had no effect on ischemic events (composite of death, myocardial infarction, and unstable angina; (Chi2=0.574; P=0.45) or the composite of death, myocardial infarction and cerebrovascular accident (Chi2=0.065; P=0.80). Patients receiving anakinra had increased injection site reactions (20.2% vs 3.6%; P=0.005) but no change in infections (14.3% vs 9.1%, P=0.435) versus placebo. Conclusions: Treatment with anakinra for 14 days following STEMI blunts the inflammatory response and appears to reduce the occurrence of HF events at 1 year. These results support the hypothesis that early and targeted modification of the inflammatory response in STEMI may be a viable strategy to improve patient outcomes. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Heart Lung and Blood Institute (USA), American Heart Association (USA)